Ghana Tax Gap Analysis - World Bank (World Bank, Washington, DC, 2020)
The objective of this report is to provide a comprehensive evaluation of the tax gap in Ghana, and help the Government of Ghana identify the areas where they can increase tax revenue by improving compliance. Tax gap for corporate income tax, import tax, estimated value added tax, and potential tax revenue from formalization of informal firms were investigated.